Go Jozi: Using informal trade and urbanathletics to re-imagine public space in Johannesburg's inner city - Hoffe, Stephen (My University, 2013)
This thesis is an exploration of a new public space in the inner city of Johannesburg which attracts new people and becomes a catalyst for futer renewal and development. For this purpose the focus of my design methodology becomes the re-imagining of public space so as to achieve an iconic and unique space within the city. Two urban user groups who re-imagine urban space through their actions become my primary case studies. This group is made up of urban athletes and informal traders, who form the core of this thesis. For this reason my first step becomes the understanding of how these groups re-imagine space. This is achieved by studying and analysing their practices in the inner city of Johannesburg. With this documented I can discuss their potential as a resource for the design of a new public space in the city. First, however, I will establish, and discuss, the social and physical context of this new space by looking at Johannesburg’s historical and present day spatial makeup. This will ultimately validate my proposal and site selection. The design process begins with relevant public space precedent studies, followed by the definition of a programme and brief. These are carried forward into the design of my scheme, which includes a large plaza and supplementary building. The document will close with the design drawings and models.